If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 8q = 5 + 7q Solving 3 + 8q = 5 + 7q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-7q' to each side of the equation. 3 + 8q + -7q = 5 + 7q + -7q Combine like terms: 8q + -7q = 1q 3 + 1q = 5 + 7q + -7q Combine like terms: 7q + -7q = 0 3 + 1q = 5 + 0 3 + 1q = 5 Add '-3' to each side of the equation. 3 + -3 + 1q = 5 + -3 Combine like terms: 3 + -3 = 0 0 + 1q = 5 + -3 1q = 5 + -3 Combine like terms: 5 + -3 = 2 1q = 2 Divide each side by '1'. q = 2 Simplifying q = 2
| 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 | | 5y+2(y-4)=5(y+1)-2 | | 4(y+1)+5=(y-1)+y | | -3x-6y=17 | | 6x+10=x+25 | | 8x-(2x+4)=38 |